Transformation of travel literature on television (on the example of I. Melezh’s TV program «Traveling around Europe» (1956)) - Morozowa, Elena I. (Journal of the Belarusian State University. Journalism, 2019)
For the first time the article explores the work of I. Melezh as a television publisher. It is determined that the writer became a pioneer of the travel essay genre on Belarusian television. The techniques and principles, that I. Melezh used to adapt the printed text to the audiovisual space, in particular, the announcement, dialogized monologue, reducing the number of typical characters, autobiographical episodes, contrast, comparison, and the principle of subjectivism, the principle of co-creation of the author and the audience, are highlighted. They can be used in modern television production to improve the quality and competitiveness of programs.